PP.20.30: ASSOCIATION BETWEEN VASCULAR STIFFNESS AND MATRIX METALLOPROTEINASE 9 IN HYPERTENSIVE INDIVIDUALS. (June 2015) - Vilela-Martin, J.; Cosenso-Martin, L.; Mariana-Valente, F.; Giollo-Junior, L.; Lacchini, R.; Tanus-Santos, J.; Yugar-Toledo, J.; Mota-Gomes, M.
Abstract : Objective: Hypertension presents multifactorial physiopathogenic characteristics, which may modify vascular structure. The vascular stiffness and enzymes, such as extracellular matrix metalloproteinases (MMP), may cause endothelial dysfunction, situation that increases the cardiovascular risk profile. Objective: This study aimed a) to correlate socio-demographic factors and biochemical levels of MMP-9; b) to evaluate the association between markers of vascular stiffness, represented by augmentation index (AI) and central blood pressure (BP), and levels of MMP-9 in hypertensive (HT), prehypertensive (PH) and normotensive (NT) individuals. Design and method: We studied 40 healthy NT, 50 PH, and 44 HT (hypertensive individuals in outpatient treatment and with controlled blood pressure levels). Pre-hypertensive individuals were characterized when SBP was 120 to 139 mmHg and/or DBP 80 to 89 mmHg. Controlled hypertension was defined when SBP < 140 mmHg and/or DBP < 90mmHg in antihypertensive treatment. Blood was collected for biochemical analysis and measurement of MMP-9. MMP-9 concentrations are given in ng/mL. Vascular stiffness was assessed by the applanation tonometry (OMRON HEM-9000AI). Comparison between groups was performed by Kruskal-Wallis and Dunn Tests. Value-p < 0.05 was considered significant. Results: Mean age was 56.6 ± 7.4 for HT, 48.1 ± 9.2 for PH and 40.4 ± 7.9 years for NT (p < 0.0001). There was difference of MMP-9 among the groups (p = 0.04). The statistical difference occurred between PH and HT (125.6 x 95.4 ng/ml; p = 0.03), but no difference between NT and PH (120.5 x 125.6 ng/ml; p = 0.68), and between NT and HT (120.5 x 95.4 ng/ml; p = 0.9). The systolic blood pressure (SBP) was higher in HT group in comparison to prehypertensive group and it was also higher in the PH than normotensive group (p < 0.05). The SBP correlated with values of MMP-9. MMP-9 presented association with vascular stiffness measures (central BP and AI) in the hypertensive group (univariate analysis). However, these data were not confirmed in multivariate analysis. Conclusions: SBP and central BP correlate to metalloproteinase 9 in hypertensive individuals, showing that this group evolves with greater arterial stiffness than the normotensive group. This suggests the active participation of MMP-9 in vascular remodeling, in spite of lower MMP-9 level in the hypertensive group in comparison to prehypertensive group.